Comparing trends of perinatal mortality in two rural areas of Matlab, Bangladesh. (30th September 2020) - Rahman, A; Anwar, I; Austin, A
Abstract: The study conducted in a rural sub-district, Matlab, Bangladesh among adolescent motherhood (10-19 years) in the International Centre for Diarrhoeal Disease Research, Bangladesh included total of 4, 996 adolescent mothers in the analysis. Chi-square tests and binary logistic regression were used to document adolescent pregnancy trends and the differences in and causes of perinatal death. The fertility rate was 27 per 1000 adolescent mothers in ISA and 20 per 1000 adolescent mothers in GSA, during the 9 year of study period. The adjusted odds of an adolescent mother having a perinatal death in ISA, relative to GSA was 0.69 (95% CI: 0.52 - 0.91, p-value<0.05). Significant determinants of perinatal death among adolescent mothers were: maternal education, paternal education, mothers' age at first birth, asset score and distance from nearest facility. Dr. Rahman will raise the importance of addressing these determinants in designing health policy interventions targeting this specifically vulnerable group.